A hydrological model dedicated to topography-based simulation of nitrogen transfer and transformation: rationale and application to the geomorphology- denitrification relationship - Beaujouan, Véronique; Durand, Patrick; Ruiz, Laurent; Aurousseau, Pierre; Cotteret, Gilles (Hydrological processes, 2002)
A new integrated hydrological and nitrogen model, called TNT2 (topography‐based nitrogen transfer and transformation), has been developed to study nitrogen fluxes in small catchments. This model, process‐based and spatially distributed in order to take spatial interactions into account, has been kept as simple as possible. Here, only the hydrological module is discussed. The two main hypotheses of the hydrological model are taken from the TOPMODEL concept (constant hydraulic gradient equal to slope and hydraulic conductivity decreasing exponentially with depth). The model is based on a daily water balance for each cell of a regular square grid and computes an explicit cell‐to‐cell routing. Transfer through the vadose zone is simulated using a conceptual, layer‐based algorithm analogous to the Burns model, except that a drainage water reservoir has been added to simulate mobile/immobile water processes and variations of the water table within the soil. The crop growth and nitrogen transformations are simulated using the equations of a generic plant‐soil model, STICS. As an example, a preliminary study of the effect of the catchment geomorphology on denitrification is presented. The study was performed on theoretical catchments with contrasted slope shapes and pathway patterns. Results show that the whole‐catchment denitrification depends on catchment geomorphology, although not directly through the extent of saturated areas. It is concluded that TNT2 seems to be a powerful tool to explore catchment processes, both by application to actual cases and by exploration on simple scenarios. Copyright © 2002 John Wiley & Sons, Ltd.